2011
DOI: 10.1176/appi.ajp.2010.10091340
|View full text |Cite
|
Sign up to set email alerts
|

After GWAS: Searching for Genetic Risk for Schizophrenia and Bipolar Disorder

Abstract: Ten years ago it was widely expected that the genetic basis of common disease would be resolved by genome-wide association studies (GWAS), large-scale studies in which the entire genome is covered by genetic markers. However, the bulk of heritable variance remains unexplained. The authors consider several alternative research strategies. For instance, whereas it has been hypothesized that a common disease is associated primarily with common genetic variants, it is now plausible that multiple rare variants each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
124
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(127 citation statements)
references
References 19 publications
(25 reference statements)
0
124
0
3
Order By: Relevance
“…Most recent evidence supports a combination of genetic and environmental factors contributing to the development of the disorder (Marenco and Weinberger, 2000). To date, no one gene, single-nucleotide polymorphism, or mutation has been consistently linked to the illness, and it is likely that multiple susceptibility genes create a predisposition to developing schizophrenia (Fanous et al, 2012;Gershon et al, 2011;Levinson et al, 2012). Genetics studies, which have led the way for diseases such as breast cancer and cystic fibrosis, have been much less impactful in the schizophrenia field.…”
Section: Introduction: the Problem Of Schizophreniamentioning
confidence: 99%
“…Most recent evidence supports a combination of genetic and environmental factors contributing to the development of the disorder (Marenco and Weinberger, 2000). To date, no one gene, single-nucleotide polymorphism, or mutation has been consistently linked to the illness, and it is likely that multiple susceptibility genes create a predisposition to developing schizophrenia (Fanous et al, 2012;Gershon et al, 2011;Levinson et al, 2012). Genetics studies, which have led the way for diseases such as breast cancer and cystic fibrosis, have been much less impactful in the schizophrenia field.…”
Section: Introduction: the Problem Of Schizophreniamentioning
confidence: 99%
“…Is now plausible that multiple rare variants each have a potent effect on disease risk and that they could accumulate to become a substantial component of mental disease risk 44 . The search for genetic information that are associated with the outbreak of TB involves structural and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the long term the aim will be to undertake studies similar to GWAS with very large sample sizes [113]. Until sequencing technology is inexpensive enough to perform these large sample studies various approaches have been suggested to further our understanding.…”
Section: Next Generation Sequencingmentioning
confidence: 99%